EFFECT OF PART I CLTS: OPEN DEFECATION FREE WITH DIARRHEA INCIDENCE IN OELOMIN VILLAGE KUPANG REGENCY - Faku, Noventji Abriance; Setyo Budi Susanto; Agusta Dian Ellina (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2019)
The Community-Led Total Sanitation (CLTS) is sanitation programme through community empowerment to change community hygiene and sanitation behavior. As initial phase of the activity was focused on the open defecation free program, but in fact diarrhea is still often occurred. The purpose of this study was to determine the effect of part I CLTS: open defecation free with diarrhea incidence in Oelomin Village Kupang Regency. Research design was observational with cross sectional approach. Population studied was all households in Oelomin Village Kupang Regency amount 202 households, with a simple random sampling technique obtained sample amount 134 respondents. The independent variable was Part I CLTS with a dependent variable occurrence of diarrhea. Data collection using a questionnaire. Data analysis with dummy regression test at α = 0.05. The results showed that most of the respondents had Part I CLTS in open defecation category, amount 92 respondents (68.7%) and the majority of respondents had diarrhea in not occurred category, amount 84 respondents (62.7%). The analysis results known p-value (0,000) <a (0.05) so H0 rejected and H1 accepted, which means there is effect of part I CLTS: open defecation free with diarrhea incidence in Oelomin Village Kupang Regency. The CLTS programme affects reduction in the incidence of diarrhea because it reduces the factors that can be a place for developing germs that cause diarrhea yet not yet fully able to prevent diarrhea so it needs to be continued with the CLTS programme on the next part of washing hands with soap to prevent di sease.